Strategi Guru Dalam Mengembangkan Kecerdasan Naturalis Anak Melalui Pembelajaran Kontekstual di RA Al Ikram Islamic School Medan - Siti Aisyah Ginting; Rika Widya; Salma Rozana (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Contextual learning is an approach that links the subject matter with the real world situation experienced by students. This approach aims to improve students' concept understanding and critical thinking skills. This article discusses the application of teacher strategies in developing learners' naturalistic intelligence through contextual learning at RA Al-Ikram Islamic School. Contextual learning is an approach developed with the aim that the learning process runs actively, productively and has meaning in students' lives. Not only emphasizing on cognitive knowledge but also on affective and psychomotor. This research is a descriptive qualitative research with data sources derived from interviews and data validity assurance techniques using triangulation. The subjects came from teachers at RA Al-Ikram Islamic School Kota Medan and the Principal. This research was conducted with each stage, namely planning, implementation and observation.